The fine line between deliberate play and deliberate practice within talent development in grassroots football: evidence from a one-year longitudinal case study - Hanstad, D. V.; Skille, E. Å.; Johansen, B. T.; Strittmatter, A.-M. (Frontiers in Sports and Active Living, 2026)
Introduction: While former studies into talent development in football have considered elite clubs and retrospective studies, this single-case study provides detailed data on the training activities of a 13-year-old male football player in a grassroots club who later became a professional at the highest level in Norway.